Analysis Of Abuse Of Authority By Civil Servants In Corruption Crimes (Decision Study No. 141/Pid.Sus-Tpk/2024/Pn Mdn) - Diva Sadarta Tarigan; Aulia Rahman Hakim Hasibuan; Syahranuddin Syahranuddin (Fakultas Hukum Dehasen, 2026)
This study aims to examine the legal framework governing the abuse of authority by civil servants acting jointly in receiving gifts within corruption offenses, as well as to conduct a juridical analysis of the elements of “Abuse of Authority” and “Joint Acceptance of Gifts” as corruption crimes in Decision Number 141/Pid.Sus-TPK/2024/PN Mdn. This research employs a normative legal method with a descriptive approach, carried out through library research by examining primary, secondary, and tertiary legal materials, including the Anti-Corruption Law and the Criminal Code. The results of the study indicate that, normatively, the regulation concerning abuse of authority and the acceptance of gifts by civil servants has been clearly stipulated under Article 11 and Article 12B of Law Number 31 of 1999 as amended by Law Number 20 of 2001, which classifies such acts as formal offenses. In the context of participation, criminal liability for perpetrators acting jointly refers to the doctrine of participation (medepleger) under the Criminal Code, which requires a unity of intent and conscious cooperation. In Decision Number 141/Pid.Sus-TPK/2024/PN Mdn, the panel of judges held that all elements were fulfilled based on the defendant’s status as a civil servant, the receipt of money related to official authority, and the repetitive nature of the acts. However, substantively, there is a lack of in-depth elaboration regarding the causal relationship between the concrete authority of the office and the receipt of gifts. In addition, there is an imbalance between the term of imprisonment and the amount of restitution imposed, raising issues of proportionality in sentencing. Therefore, consistency in juridical reasoning and the application of the principle of proportionality are necessary to strengthen the effectiveness of law enforcement in corruption cases.